Bridging Faith and Land: The Unifying Power of Religion in Defending Community’s Territory - Ady, Wildan Syahamata; Mukav, Yusril Asadudin; Putra, Zippo Surya Anggara (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2022)
Land dispute conflicts in Indonesia, such as those in Kendeng and Wadas, Central Java, involving the Semen Indonesia factory, the mining, and indigenous communities, persist as they strive to protect their land, which serves as their primary source of livelihood. This research examines the role of religion in fostering unity among the Wadas community as they defend their territory amidst the land dispute with the mining industry. Using a socio-legal normative research method, this study analyses relevant regulations pertaining to territorial disputes in Indonesia while adopting a socio-legal approach to comprehend the multifaceted role of religion in territorial defense from social, cultural, and structural perspectives within Indonesian society. Primary data is collected from primary, secondary, and tertiary legal sociology materials, complemented by secondary data obtained through literature studies. The findings reveal that the people of Wadas employ religious functions as a means to safeguard their territory. By shedding light on the role of religion in fostering community unity during land dispute conflicts, this research contributes to an enhanced understanding of effective territorial defence strategies.